Synthesis and characterization of novel soluble phthalocyanines with fused conjugated unsaturated groups - KOCA, ATIF (ELSEVIER SCI LTD, 2011)
The synthesis, characterization, voltammetric and spectroelectrochemical properties of a novel tetra-cationic metallophthalocyanine (M = Zn) containing four Schiff's base substituents attached directly on peripheral positions have been presented in this work. The new compounds have been characterized by using elemental analysis, FTIR, H-1 NMR, UV-Vis and MALDI-TOF MS spectroscopic data. The electrochemical, in-situ spectroelectrochemical, and in-situ electrocolorimetric measurements on precursors and end products confirm that the complexes exhibit extra electron transfer reaction assignable to the electroactive nitro, amine and Schiff's base groups in addition to the common Pc ring-based processes. Extra conjugation of amine and cinnamaldehyde groups causes both a bathochromic shift (ca. 30 nm) in Q-band maxima and a lower redox potential (ca. -400 mV) in CV measurements. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Tetraamino phthalocyanine; Organic light emitting diode; Schiff base; Extended pi-conjugation; Spectroelectrochemistry; IN-SITU; ELECTROCHEMICAL-BEHAVIOR; ZINC-PHTHALOCYANINE; METAL-COMPLEXES; THIN-FILMS; PORPHYRAZINES; REDUCTION; BEARING; NITRO